THE EFFECT OF STAINLESS STEEL WIRE IMMERSION IN COCONUT WATER TO RESILIENCE CHANGE - Dwiki Azhar; Diana Wibowo; Fajar Kusuma Dwi Kurniawan (FKG Unlam, 2018)
Background: Orthodontic treatment is used to repair malocclusion. It is divided into fix and removable orthodontic and mostly use wire for the treatment. The wire that used in orthodontic treatment is austentic stainless steel type 304. Drinks that has low pH, such as coconut water may affect the stainless steel wire resilience. Objective: To determine the resilience effect of orthodontic wire that immersed in coconut water. Methods: This research was true experimental research with pre test and post test control group design use simple random sampling consisted of 2 groups. Control group was saline solution and treatment group was coconut water. Each group had 11 samples. Ortodontic wire 0.06 mm was cut along 3 cm and scratched. Measurement of the resilience wire was conducted before immersion and after immersion for 13 hours with temperature 37oC. Result: The study showed that wire resilience on saline solution before immersion and after immersion was 17,60 gram/mm. Wire resilience on coconut water before immersion was 17,60 gram/mm and after immersion was 17,59 gram/mm. The results of Dependent T test was p=0.167 (p> 0.05) and the test results of Independent T test was p=0.837 (p> 0.05). Conclusion: There is no effect of stainless steel orthodontic wire immersion in coconut water to the change of resilience.